Work-Culture for Employee Work-Behaviour: Mediating Role of Satisfaction - Gautam, Prakash Kumar (PYC Nepal Journal of Management, 2020)
Culture is the enduring set of values, beliefs and work principles guiding overall organizational behaviour. Employees’ behaviours are the consequences of work-culture as they behave reciprocal of their experience. This study establishes unique relationship among work-culture, employee satisfaction and work-behaviour in Small and Medium Enterprise (SMEs). Structured questionnaire was used to collect the data from 376 respondents. Confirmatory Factor Analysis was used to examine the model significance with validity, regression analysis to test the direct relationship while Preacher and Hayes Process Macro approach for examining mediation effect. This study revealed the work-culture significantly influenced employees’ satisfaction and work-behaviour with no moderation effect of job satisfaction. Findings of this study suggest managers to promote supportive work-culture to increase employee satisfaction and positive work-behaviour. This study also provides evidence to strengthen a reciprocity approach of social exchange theory (SET) in employees’ work-behaviour in SMEs.